2020
DOI: 10.1016/j.neuropsychologia.2019.107306
|View full text |Cite
|
Sign up to set email alerts
|

Prominence marking in parkinsonian speech and its correlation with motor performance and cognitive abilities

Abstract: ObjectivesResearch suggests that people with Parkinson's disease (PwPD) do not only suffer from motor but also non-motor impairment. This interdisciplinary study investigated how prominence marking is influenced by problems on the motoric and cognitive level. Materials and methodsWe collected speech production data from 38 native German speakers: 19 PwPD (under medication) with a mild to moderate motor impairment, 13 males and 6 females (mean 66.2 years old, SD = 7.7), and 19 healthy age-and gender-matched con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 83 publications
1
25
0
Order By: Relevance
“…This is in line with highlighting strategies reported for prosodic prominence in German [ 38 ]. As shown before by Thies et al [ 57 ], hyper-articulation of vowels would be expected. However, no spatial modifications were found with respect to more peripheral vowel formant frequencies (no hyper-articulation).…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…This is in line with highlighting strategies reported for prosodic prominence in German [ 38 ]. As shown before by Thies et al [ 57 ], hyper-articulation of vowels would be expected. However, no spatial modifications were found with respect to more peripheral vowel formant frequencies (no hyper-articulation).…”
Section: Discussionsupporting
confidence: 55%
“…It postulates that prominence marking can vary from speakers with PD compared to healthy controls [ 55 , 56 ]. Moreover, a recent study by Thies and colleagues [ 57 ] showed that patients with PD can mark prosodic prominence by modulating f 0 , intensity and vowel articulation in prominent positions, but the prosodic modifications are less efficient than in healthy control speakers. While patients performed with a reduced vowel space in terms of hypoarticulated vowels, they hyperarticulated prosodic parameters such as intensity and tonal range.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations